IN SILICO ANALYSIS OF BURKHOLDERIA PSEUDOMALLEI PROTEOME TO PREDICT POTENTIAL VACCINE CANDIDATE PROTEINS - RAVINDER SINGH (International Journal of Pharma and Bio Sciences, 2015)
Burkholderia pseudomallei is a Gram-negative pathogen that is the causative agent of melioidosis predominantly in South East Asia and tropical Australia. There is currently no vaccine available against Burkholderia species and available prophylactic measures have limitations. In this study, potential vaccine candidates against B. pseudomallei were predicted by in silico analysis of its proteome using Vaxign, the bioinformatic tool. Proteins localized extracellular and in outer membrane with adhesion probability of 0.5 or more, number of trans-membrane helices less than 2 and dissimilar with human and mouse proteome were selected. 58 proteins were predicted as potential vaccine candidates that may help in designing effective vaccines.